TOXICOLOGICAL PROFILING OF METHANOLIC AND AQUEOUS EXTRACTS OF AMORPHOPHALLUS COMMUTATUS VAR. WAYANADENSIS - ENDANGERED MEDICINAL PLANT IN RODENT MODELS - RAJ, SREENA; ANN BABU, MERLENE; JALEEL, V. ABDUL; GOTHANDAM, K M (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Amorphophallus commutatus var. wayanadensis (ACW) is exclusive endemic of Wayanad has been used among the traditional medicinal healers of tribal communities of Wayanad for the treatment of various ailments. Our aim of the study is to evaluate the toxicity profile of ACW is by acute and sub-acute in rodents. Â Methods: In acute toxicity studies, mice were orally administered of single doses of 1000 and 2000mg/kg of methanolic and aqueous extract and sub-acute toxicity studies were performed by administration of 200 and 400mg/kg orally for 28 days. Results: In acute toxicity studies, administration of methanolic and aqueous extract didn't observe any signs of mortality or toxicity upto 2000mg/kg body weight. No significant change in the physical, biochemical, hematological and histopathology analysis were observed for methanolic and aqueous extracts by sub-acute toxicity studies. Conclusion: The methanolic and aqueous extract of Amorphophallus commutatus var. wayanadensis is relatively safe for long term oral administration fulfilling the basic priority for its use in traditional medicinal therapies.